Beyond the dimensional limitation in bio-inspired composite: Insertion of carbon nanotubes induced laminated Cu composite and the simultaneously enhanced strength and toughness. (April 2018) - Meng, Linglong; Wang, Xiaojun; Ning, Jiangli; Hu, Xiaoshi; Fan, Guohua; Wu, Kun
Abstract: Metal/reinforcement nanolayered composites can effectively balance the strength and toughness. However, the difficulty of inserting nanoscaled metal layers restricts their practical application. In this study, laminated carbon nanotubes (CNTs) reinforced Cu composites with microscaled metal layered were fabricated by a feasible method and exhibited simultaneously enhanced strength and toughness. CNTs were deposited on Cu foils by electrophoretic deposition with two-dimensional homogeneous dispersion. Insertion of CNTs induced the laminated Cu composite with repeated layer spacing of ∼20 μm through hot pressing and hot rolling. Simultaneously enhanced yield strength (183 MPa) and elongation (30.9%) were obtained with only 0.067 vol% CNTs. The strength improvement reached far beyond the mixture rule in metal matrix composites (MMCs) with homogeneous CNTs dispersion. CNTs and the induced interfaces serve as effective dislocations motion barriers and strengthen the composite. Laminated composite exhibited more stable deformation due to suppressed strain location by the layered structure. This work highlights the strengthening and toughening effects of laminated structure induced by CNTs, and provides a feasible method to build the laminated MMCs with adjustable metal layer thickness and CNTs amount, thus breaking the dimensional limit of metal layers in the design of laminated MMCs with enhanced mechanical properties. Graphical abstract: Image 1